Pulmonary arterial hypertension associated with abatacept treatment for rheumatoid arthritis: A case report. Issue 1 (2nd January 2018) - Promislow, Steven; Mielniczuk, Lisa M.; Chandy, George; Stewart, Duncan J.; Pugliese, Carolyn; Davies, Ross A.
ABSTRACT: Abatacept (Orencia®, Bristol-Myers Squibb Canada) is a selective T-cell co-stimulation modulator that has an emerging role in the treatment of rheumatoid arthritis (RA). We present a case of a patient with RA who developed severe pulmonary arterial hypertension (PAH) after exposure to abatacept therapy. To our knowledge, this is the first case describing a possible association between abatacept and the development of PAH. A causal link between abatacept and PAH is not clear, but ongoing monitoring by physicians prescribing abatacept is important to monitor for other instances of this potentially serious complication. RÉSUMÉ L'abatacept (Orencia®, Bristol-Myers Squibb Canada) est un modulateur sélectif de la costimulation des cellules T qui a un rôle émergent dans le traitement de l'arthrite rhumatoïde. Nous présentons le cas d'un patient atteint d'arthrite rhumatoïde qui a commencé à souffrir d'hypertension artérielle pulmonaire grave après un traitement par abatacept. À notre connaissance, il s'agit du premier cas décrivant une association possible entre l'abatacept et la survenue de l'hypertension artérielle pulmonaire. Il n'existe pas de lien causal clair entre l'abatacept et l'hypertension artérielle pulmonaire, mais il est important que les médecins qui prescrivent de l'abatacept effectuent un suivi continu pour surveiller l'apparition d'autres cas présentant cette complication potentiellement grave.